2016
DOI: 10.1016/j.jmb.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Salt Effects on the Thermodynamics of a Frameshifting RNA Pseudoknot under Tension

Abstract: Because of the potential link between −1 programmed ribosomal frameshifting and response of a pseudoknot (PK) RNA to force, a number of single-molecule pulling experiments have been performed on PKs to decipher the mechanism of programmed ribosomal frameshifting. Motivated in part by these experiments, we performed simulations using a coarse-grained model of RNA to describe the response of a PK over a range of mechanical forces (fs) and monovalent salt concentrations (Cs). The coarse-grained simulations quanti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 61 publications
7
25
0
Order By: Relevance
“…The heat capacities have two distinct peaks, which indicate there is at least one intermediate between the unfolded and folded states. This finding is consistent with previous experimental and simulation studies [28,48,49]. From the position of the peaks, we determined the two melting temperatures, T m1 and T m2 , whose values are listed in Table I.…”
Section: Resultssupporting
confidence: 90%
“…The heat capacities have two distinct peaks, which indicate there is at least one intermediate between the unfolded and folded states. This finding is consistent with previous experimental and simulation studies [28,48,49]. From the position of the peaks, we determined the two melting temperatures, T m1 and T m2 , whose values are listed in Table I.…”
Section: Resultssupporting
confidence: 90%
“…48,49 Our previous study also showed that the thermal and mechanical (un)folding occur predominantly through the I1 state. 47 The present results show that I1 state is not only thermodynamically stable, but also is the major kinetic intermediate.…”
Section: Resultssupporting
confidence: 54%
“…This finding is consistent with previous experimental and simulation studies. 27,46,47 From the position of the peaks, we determined the two melting temperatures, T m1 and T m2 , whose values are listed in Table 1. It should not go unnoticed that the melting temperatures, T m1 and T m2 , for the hTR HP are in excellent agreement with experiments, demonstrating the effectiveness of TIS model in predicting the thermodynamic properties of RNA.…”
Section: Resultsmentioning
confidence: 99%
“…To arrive at an accurate model, which reliably predicts the thermodynamic properties of large RNA molecules, we first began with a sequence-dependent three-interaction site (TIS) coarse-grained (CG) model for nucleic acids (24), which has been adopted to study a range of problems related to RNA folding (2,10,(25)(26)(27)(28)(29)(30)(31)(32). Even with this simplification, the inclusion of both monovalent ions (present in excess concentration relative to divalent cations) and divalent ions explicitly is computationally demanding, although folding simulations of a 195-nt Azoarcus ribozyme and pseudoknots have been carried out successfully (10,33).…”
mentioning
confidence: 99%